EKUITAS MEREK PRODUK MINUMAN SERBUK BUAH INSTAN - Suryaningsih, Ika Barokah; Prayogo, Hary (BISMA: Jurnal Bisnis dan Manajemen, 2011)
This research seeks to identify consumer’s response toward brand equity instan soft drink fruit-powder Nutrisari and Marimas. This is a descriptive research based on primary data collected from respondent throughout questionaire. To test validity and reliability this study uses Pearson product moment, avarage and standard deviation, Cohran test, performance importance diagram, brand loyalty piramida and brand switching patern matrix. Result shows that Nutrisari is abrand that has ability to top of mind while Marimas has only able to be brand recall from the costumer’s mind. In a specific brand association, only Marimas passes all association test. In term of brand perceived quality, all of those three brands have higher performance compared to their importancenya. In the brand loyalty level, Nutrisari and Marimas have ideeal piramid for brand loyalty that is rolled back triangle.